A REVIEW OF ESTIMATION OF SOFTWARE PRODUCTS DEVELOPMENT COSTS (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2017)
In the modern business and management of business processes, the standardization of procedures allows the creation of added value, increasing competitiveness and success in the business of an organization. Evaluation of the budget for software development is crucial to the success of an IT project, because the inability to make a realistic assessment leads to inadequate project plans, customer dissatisfaction, poor quality of software products, and reduced profits. In order to minimize such situations, making accurate and reliable software cost estimation should be carried out at all stages of the project life cycle. Although hundreds of research articles focusing on the application of different methods of budget estimates of the software product have been published so far, there is no comprehensive review of the current situation or review of research trends in the budget estimates of the software product. This paper aims to create a framework for estimation of costs of development of software products by providing an overview of the most influential researchers, the most influential articles published in the WoS database, the most used keywords for searching the articles, as well as a review of the estimation techniques used in budget estimates of the software product.Keywords:  Software cost estimation, software cost prediction, keyword analysis, estimation techniques